How competition in investing, hiring, and selling affects (un)employment: An analysis of equilibrium scenario - Siegfried Berninghaus; Werner Güth; Hans Jürgen Ramser (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 1999)
Most models of labor markets and (un)employment neglect how competition among firms or sectors of the economy affects their hiring of workers and working times. Our approach pays special attention to such effects by proposing a complex stage game where firms invest in capital equipment before hiring workers. Working times are adjusted to demand which is implied by price competition. A special advantage of such a framework is that one can distinguish two kinds of employment effects, namely the numbers of workers as well as their working times, and that one can locate which firm or sector suffers from unemployment. Instead of solving the model in full generality we offer several equilibrium scenarios showing that certain economic phenomena are consistent with subgame perfect equilibrium behavior.
urn:nbn:de:kobv:11-10046895
Keywords: 330